Henoch-Schonlein Purpura—A Case Report and Review of the Literature - Amit B. Sohagia; Srinivas Guptha Gunturu; Tommy R. Tong; Hilary I. Hertan (Gastroenterology Research and Practice)
We describe a case of an adolescent male with Henoch-Schonlein purpura (HSP), presenting with cutaneous and gastrointestinal manifestations. Endoscopy revealed diffuse ulcerations in the stomach, duodenum, and right colon. Biopsies revealed a leukocytoclastic vasculitis in the skin and gastrointestinal tract. Steroid therapy led to complete resolution of the symptoms. HSP is the most common childhood vasculitis, and is characterized by the classic tetrad of nonthrombocytopenic palpable purpura, arthritis or arthralgias, gastrointestinal and renal involvement. It is a systemic disease where antigen-antibody (IgA) complexes activate the alternate complement pathway, resulting in inflammation and small vessel vasculitis. Mild disease resolves spontaneously, and symptomatic treatment alone is sufficient. Systemic steroids are recommended for moderate to severe HSP. The prognosis depends upon the extent of renal involvement, which requires close followup. Early recognition of multiorgan involvement, especially outside of the typical age group, as in our adolescent patient, and appropriate intervention can mitigate the disease and limit organ damage.